2021
DOI: 10.1021/acscatal.1c00752
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Nucleophilic Role of Metal–Boryl Complexes in Borylation Reactions

Abstract: Transition metal–boryl complexes play an important role as reactive intermediates in catalytic borylation processes and have enjoyed tremendous exploration. Over the years, it has been well established that a boryl ligand possesses strong nucleophilicity in copper­(I)–boryl complexes. Thus, the role played by boron’s “empty” p orbital has often been overlooked and d-electrons’ effect from the metal is even more seldom mentioned, despite the fact that they in theory should also have influence on the reactivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…Finally, the electron distribution in the Cu–B bonds was investigated, since studies attribute the high nucleophilicity and reactivity exhibited by these complexes to the Cu-boryl σ-bonding electrons. Computational work by Carbó and Fernández in 2012, 33 and Sheong and Lin in 2021, 34 revealed that the contribution of B-based orbitals to the M–BR 2 bond is remarkably high ( ca. 70%, with a p/s ratio ≈ 0.9) 35 in the case of mononuclear Cu-boryl species, whereas in other examples like Au- or Pd-boryl compounds, the contribution of B is 56% and 53%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the electron distribution in the Cu–B bonds was investigated, since studies attribute the high nucleophilicity and reactivity exhibited by these complexes to the Cu-boryl σ-bonding electrons. Computational work by Carbó and Fernández in 2012, 33 and Sheong and Lin in 2021, 34 revealed that the contribution of B-based orbitals to the M–BR 2 bond is remarkably high ( ca. 70%, with a p/s ratio ≈ 0.9) 35 in the case of mononuclear Cu-boryl species, whereas in other examples like Au- or Pd-boryl compounds, the contribution of B is 56% and 53%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, gold-boryl complex III involving aryl substituents is expected to differ from typical dioxy- and diamino-boryls such as Bpin (pin = pinacolate: 2,3-dimethyl-2,3 butanediolate), Bcat (cat = 1,2-O 2 C 6 H 4 ), Bneop (neop = (OCH 2 ) 2 CMe 2 ), Bdan (dan = 1,8-diaminonaphthalene), etc., mainly in the role played by boron’s “empty” p orbitals and to exhibit stronger Lewis acidity at the boron center. 4 Although experimental evidence for the reaction of complex III with carbon dioxide has not been reported, the reduction of CO 2 to CO catalyzed by a copper boryl complex [IPrCu(Bpin)] has been observed to occur in solution under mild conditions, 5 and the reaction mechanism has been computationally studied. 6 Very recently, some of us have computationally investigated the analogous reactivity with isostructural gold-aluminyl, gold-gallyl, and gold-indyl complexes, [ t Bu 3 PAuX( Si NON)] − (X = Al, Ga, and In, Si NON = [O(SiMe 2 NDipp) 2 ] 2– , Dipp = 2,6- i Pr 2 C 6 H 3 ), demonstrating that this is kinetically and thermodynamically favorable only for the gold-aluminyl complex.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction insertion of the metal‐complex occurred at the more nucleophilic site of the double bond. As described in the literature, when the boryl in the metal complex is not substituted with a π‐donating group, the empty p orbital of boron remains active and can serve as the electrophilic site [12] . The C−H borylation of aromatics is well documented, in contrast fewer studies described analogous reactions for alkenes.…”
Section: Resultsmentioning
confidence: 99%
“…As described in the literature, when the boryl in the metal complex is not substituted with a π-donating group, the empty p orbital of boron remains active and can serve as the electrophilic site. [12] The CÀ H borylation of aromatics is well documented, in contrast fewer studies described analogous reactions for alkenes. However, we assume that the insertion reaction occurred with an in situ generated tris(boryl)Ir(III) complex as depicted in the literature.…”
Section: Resultsmentioning
confidence: 99%